Terminological problems in Georgian translations of European standards of education - Jikia, Ia (Actual Problems of Kartvelology, 2013)
After completing the Russian mono-ideology Georgia has taken pro-Western course. Now the Georgian education system is closely related to the European Higher Education Area (EHEA)-the Bologna process. Georgia joined Bologna Process in 2005 at Bergen Summit. The Bologna declaration was preceded by such documents as: Magna Chartum Universitatum (1998); Lisbon Convention (1997); Sorbona Declaration (1998). This hassled to the need of translation the main documents of the Bologna Process from different languages: English, German, French, etc. For this purpose the compilation of English-Georgian Multilingual Dictionary of Higher Education was initiated and is now in progress. Our research interests have focused on the translation of the Bologna Process documents. With the spread of globalization and the Bologna process the problem of harmonization of terminology is up-to-date. We research the concepts, terminology, newly formed lexical units, terminological doublets, variants, full synonyms, language etiquette, orthographic variants and other problems of the language. Instead, the term is paraphrased, or hasty, tentative "translations" of the unknown terms are employed. It is important to analyze contemporary linguistic situation and determine which term has been established and standardized, which standards are approved by the state commission. This research will assist the unification of the norms through which the rich traditions of studying and functioning of the Georgian literary language will be continued.